Deficiency of eIF4B Increases Mouse Mortality and Impairs Antiviral Immunity - Chen, Biao; Chen, Yuhai; Rai, Kul Raj; Wang, Xuefei; Liu, Shasha; Li, Yingying; Xiao, Meng; Ma, Yun; Wang, Guoqing; Guo, Guijie; Huang, Shile; Chen, Ji-Long (Frontiers in Immunology, 2021)
Eukaryotic translation initiation factor 4B (eIF4B) plays an important role in mRNA translation initiation, cell survival and proliferation in vitro. However, its function in vivo is poorly understood. Here, we identified that eIF4B knockout (KO) in mice led to embryonic lethality, and the embryos displayed severe liver damage. Conditional KO (CKO) of eIF4B in adulthood profoundly increased the mortality of mice, characterized by severe pathological changes in several organs and reduced number of peripheral blood lymphocytes. Strikingly, eIF4B CKO mice were highly susceptible to viral infection with severe pulmonary inflammation. Selective deletion of eIF4B in lung epithelium also markedly promoted replication of influenza A virus (IAV) in the lung of infected animals. Furthermore, we observed that eIF4B deficiency significantly enhanced the expression of several important inflammation-associated factors and chemokines, including serum amyloid A1 (Saa1), Marco, Cxcr1, Ccl6, Ccl8, Ccl20, Cxcl2, Cxcl17 that are implicated in recruitment and activation of neutrophiles and macrophages. Moreover, the eIF4B-deficient mice exhibited impaired natural killer (NK) cell-mediated cytotoxicity during the IAV infection. Collectively, the results reveal that eIF4B is essential for mouse survival and host antiviral responses, and establish previously uncharacterized roles for eIF4B in regulating normal animal development and antiviral immunity in vivo.